Socioeconomic impact of the oil spill on community participation in the clean-up operations and resilience in Imo State, Nigeria - Okpechi, Isidiho Alphonsus (2021)
This study of causes and socioeconomic impact of the oil spill on community participation in the clean-up operations and resilience in Ohaji/Egbema and Oguta regions of Imo State, Nigeria is necessary considering the adverse impact of oil spill on these communities. These two local government areas share similar demographic and environmental characteristics, where crude oil is drilled, and disastrous oil spill occurs most often by human-made actions. The stakeholder’s theory, crisis management theory and participatory theory are three theories employed in this study to reflect the participation of local people, the oil companies, and government as stakeholders, and their management of crisis that emanated from the oil spill. Mixed method approach was employed in this study. The research design was a case study where the qualitative part applied purposive in-depth interviews on 13 informants, in which the ensuing data analysis used transcription, coding, thematizing and writing out the report. Meanwhile, the quantitative part employed the survey data collection technique where a total of 376 questionnaires were administered on adult respondents aged 18-69 before the data being analyzed to support the qualitative findings. Interview results supported by survey data showed that the main causes of oil spills included corrosion of ageing facilities having the highest frequency (32.5%), followed by equipment malfunctions (15.2%), natural causes (10.6%) and operation or maintenance errors (10.3%). The in-depth interview demonstrated that the community faced sadness and hardship due to loss of income resulting from the oil spill on farmlands and water. This study found that communities actively participated in oil spill responses through identification of the spills, clean-up operations, monitoring and evaluation of the works, and law implementation. Regrettably, the legislations did not help in reducing the impacts of oil spill because of the poor law enforcement, high corruption, and lack of political will. Health hazards caused by the polluted environment as highlighted by the informants has caused sicknesses such as general weaknesses, cough, headache, vomiting, blisters, stomachache, and fever among those who participated in the spilled-oil clean up and those living closer to the spill locations. The little or non-compensation for the affected families further increased their levels of poverty, sickness, and psychological stress. As resilience to cope with difficulties, many of the fish farmers constructed fishponds in their compounds or closer to their homes, while other community members changed their occupations from fishing and crop farming to other activities such as trading, welding, and motorcycle taxi service. Decline in moral standards displayed by disunity, confrontation, and lack of trust amongst the community members also led to decline in human and social capitals, forcing people to engage in illegal and immoral making money activities for survival. Empirically, the negative impacts of oil-spill were found highest for psychological stress and environmental damage, followed by cultural impact, while the children’s education impact and level of benefit sharing (compensation) were low. The analysis of Spearman’s correlation showed that cultural change was positively associated with children’s education and environmental impacts, while high psychological stress was associated with low benefit sharing (compensation) and more cultural change. In conclusion, the oil spill in Imo State caused adverse impacts such as environmental pollution and loss of income, which triggered psychological stress, severe health hazards, cultural changes and moral upheaval, and occupational displacement on the local communities. Despite communities' active participation in the clean-up operations and their resilience in facing challenges, the government is urged to consider the implementation of oil spill laws more seriously to ensure that oil companies are held accountable for the crisis and pay adequate compensation to the affected communities.